Strategi Guru PAI Dalam Meningkatkan Kemandirian Belajar Siswa di SMPN 1 Corawali Kabupaten Sidrap - Salsyabila, Hasnia; Syahid, Akhmad; Akil, Muh; Mustamin, Mustamin; Raehana, Syarifa; Wahab, Abdul (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to identify and analyze the strategies of Islamic Religious Education (PAI) teachers in improving the learning independence of grade IX students at SMPN 1 Corawali, Sidrap Regency. Learning independence is a crucial aspect in the education process, especially PAI learning which emphasizes the development of character and religious values. This qualitative study uses data collection methods in the form of observation, in-depth interviews, and document analysis. Management of learning independence is carried out through structured task schedules and periodic feedback, as well as encouraging student involvement in worship practices. Despite facing challenges such as low student motivation and dependence on friends, teachers continue to try to overcome these obstacles. Overall, the strategies implemented have proven effective in shaping students' learning independence, both academically and spiritually, showing significant potential in Islamic Religious Education learning.